2001
DOI: 10.1080/02701367.2001.10608953
|View full text |Cite
|
Sign up to set email alerts
|

Parental Activity as a Determinant of Activity Level and Patterns of Activity in Obese Children

Abstract: The purposes of this study were to measure the level and pattern of moderate-to-vigorous physical activity (MVPA = > 4.5 METs) and examine predictors of activity in obese children. Fifty-one 8-12-year-old children seeking obesity treatment wore accelerometers for 3 or 4 days. Children averaged 12.2 bouts of MVPA per day that lasted an average of 4.2 min, while parents engaged in 3.9 bouts of MVPA that lasted 4.2 min. Hierarchical regression models showed parent activity improved the prediction of obese childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 49 publications
3
58
2
2
Order By: Relevance
“…However, such exposures are themselves in part likely to be mediators of the parental BMI effects since childhood diet and physical activity patterns are known to be importantly determined by parental activities. [30][31][32] Implications We have found that the majority of those who were overweight or obese at age 5 y remain overweight or obese at age 14 y and an important proportion of those who were normal at age 5 y become overweight or obese. These findings suggest that to reduce the public health burden of childhood and adolescence overweight or obesity, early prevention of childhood obesity is important.…”
Section: Study Limitationsmentioning
confidence: 99%
“…However, such exposures are themselves in part likely to be mediators of the parental BMI effects since childhood diet and physical activity patterns are known to be importantly determined by parental activities. [30][31][32] Implications We have found that the majority of those who were overweight or obese at age 5 y remain overweight or obese at age 14 y and an important proportion of those who were normal at age 5 y become overweight or obese. These findings suggest that to reduce the public health burden of childhood and adolescence overweight or obesity, early prevention of childhood obesity is important.…”
Section: Study Limitationsmentioning
confidence: 99%
“…5,6 Several studies have demonstrated that parental involvement significantly improves treatment outcome, [6][7][8][9] and parental weight change and parental activity are significant predictors of child weight change and activity. 4,[10][11][12] These data suggest that parental influences are critical determinants of children's attitudes about eating and weight loss and that a closer examination of specific parental attributes may help improve current weight-loss treatments.…”
Section: Introductionmentioning
confidence: 99%
“…4 The home environment seems to have an important function in children's physical activity and obesity risk in a number of ways. For example, parental modelling of physical activity and of sedentary behaviour is associated with children's activity levels, 5,6 their sedentary habits 7 and a greater likelihood of being overweight in girls. 8 Sibling physical activity has also been inversely associated with weight change in girls.…”
Section: Introductionmentioning
confidence: 99%